Higher fasting triglyceride predicts higher risks of diabetes mortality in US adults - Wang, Yutang (Lipids in health and disease, 2021)
It is unknown whether higher triglyceride results in higher mortality from diabetes, i.e., diabetes mortality. This study aimed to investigate the association of fasting triglyceride with diabetes mortality. This study included 26,582 US adults from the National Health and Nutrition Examination Surveys from 1988 to 2014. Diabetes mortality outcomes were ascertained by linkage to the National Death Index records. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) of triglyceride for diabetes mortality. Higher levels of fasting triglyceride were associated with higher levels of glucose, glycated hemoglobin, insulin, and homeostatic model assessment for insulin resistance at baseline. A 1-natural-log-unit increase in triglyceride (e.g., from 70 to 190 mg/dL) was associated with a 115% higher multivariate-adjusted risk of diabetes diagnosis (odds ratio, 2.15; 95% CI, 2.00-2.33). During 319,758 person-years of follow-up with a mean follow-up of 12.0 years, 582 diabetes deaths were documented. Compared with people with triglyceride in the lowest quintile, people with triglyceride in the highest quintile had an 85% higher risk of diabetes mortality (HR, 1.85; 95% CI, 1.25-2.73). A 1-natural-log-unit increase in triglyceride was associated with a 40% higher multivariate-adjusted risk of diabetes mortality. The positive association between triglyceride and diabetes mortality was also presented in sub-cohorts of participants with or without diabetes. This study demonstrated that higher fasting triglyceride was associated with a higher diabetes mortality risk.